2016
DOI: 10.4103/1735-1995.178737
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of MMP-9 and TIMP-1 proteins with chronic obstructive pulmonary disease risk: A systematic review and meta-analysis

Abstract: Background:We performed this meta-analysis in order to collect all the relevant studies to clarify the correlations of matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1) with chronic obstructive pulmonary disease (COPD).Materials and Methods:After a literature search in electronic databases, pertinent case-control studies investigating the correlations of MMP-9 and TIMP-1 protein expressions within a COPD setting were enrolled based on our strict inclusion and exclusion cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 58 publications
2
24
0
3
Order By: Relevance
“…[ 2 ] It has been shown that various immune cells and a variety of cellular and molecular pathways are involved in inflammation and play critical roles in COPD pathogenesis. [ 3 4 ] Among many cellular and molecular targets, microRNAs (miRNAs) have emerged to be involved in COPD pathogenesis. [ 5 6 ] Deregulation of miRNAs is associated with the initiation and progression of several diseases such as stroke, cardiovascular diseases, diabetes, cancer, and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] It has been shown that various immune cells and a variety of cellular and molecular pathways are involved in inflammation and play critical roles in COPD pathogenesis. [ 3 4 ] Among many cellular and molecular targets, microRNAs (miRNAs) have emerged to be involved in COPD pathogenesis. [ 5 6 ] Deregulation of miRNAs is associated with the initiation and progression of several diseases such as stroke, cardiovascular diseases, diabetes, cancer, and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-9 is inhibited by the tissue inhibitors of metalloproteinase (TIMP1) and so the imbalance between MMP-9 and TIMP1 ratio could be involved in COPD pathogenesis [28]. Herein, in complement of the MMP-9 and TIMP1 ratio analysis [28, 29], we demonstrate that the concentration of the MMP-9/TIMP1 complex in the serum of COPD patients is higher than that in healthy controls, which corroborates the findings of other authors [30]. More complexes of MMP-9/TIMP1 could be delivered by increased secretion of MMP-9, but it was also found that COPD patients exhibited a significantly higher level of unbound TIMP1 ([29, 30] and our unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicated that EGF and its receptor EGFR were increased in some tumors, such as gastric cancer, and GBM, which further induced tumorigenesis, and stimulated cell proliferation and migration [ 19 21 ]. In addition, matrix metalloproteinases are involved into cell invasion, metastases, and angiogenesi, and can cause dynamic changes of biological behaviors [ 22 25 ]. In the present work, our study showed that U87 and U251 cells transfected with miR-137 mimics indeed decreased the expression of EGFR, MMP2 and MMP9 proteins than control, suggesting that miR-137 reduced GBM cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%